An analysis of South Africa's right to board vessels within territorial waters and international waters - Robertson, Richard (Centre for Law and Society, 2026)
Boarding, in its simplest sense, refers to the embarkation onto a ship's deck of people. A boarding can either be compliant or opposed, whereby the master and crew both acknowledge and respond to law enforcement agencies or not. 1 In peacetime, boarding allows authorized inspectors of one nation or group, to examine a ship's cargo in a search for drugs, weapons, passengers who are unrecorded on the ship's manifest, or any other type of contraband that could possibly have been carried aboard. A nation's law enforcement agencies could also board any suspicious ships that have been over fishing in such a nation's territorial waters or if the vessel is suspected ofpolluting.2 South Africa has a variety of rights to board vessels at sea. The legalities of a boarding in general are complex, both international and domestic law authorise South African law enforcement agencies to board vessels, with varying jurisdictions depending on where and for what reason to board. The aim of this dissertation is to give insight to the current South African law governing the country's law enforcement agencies and their right to board, inspect and seize cargo from vessels within South African waters or upon the high seas during peacetime. An analysis of these rights will be done, which will highlight legal issues relating to boarding's that have been compounded due to a number of reasons and how South Africa can draw from other countries experiences to rectify these issues.